Identifying the type of impairments among children with disabilities: An observational study of the Divulapitiya Divisional Secretariat Area: Weerakoon W.A.S.S.*1, Gunawardhana R.M.R.2, Kaushalya H.B.D.3 and Fernando I.M.O.4 (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2025)
Children with disabilities include those who have long-term physical, mental, intellectual, or sensory impairments which, in combination with various barriers, may hinder their full and effective participation in society on an equal basis, according to the Convention on the Rights of Persons with Disabilities. The demographics of children with impairments are quite different. They include children who were born with an inheritable condition that impacts their physical, mental, or social development; those who had an infection, serious injury, or nutritional shortfall that had long-term functional effects; and those who were exposed to environmental toxins that caused learning disabilities or developmental delays. Children with impairments might also be individuals whose difficult life situations cause them to experience anxiety or sadness. There are about 240 million children worldwide who struggle with disabilities. In Sri Lanka, 1.67% of children aged 5-14 were identified as disabled in 2012. An observational study was conducted in the Divulaptiya divisional Secretariat area to understand the type of impairments among children with disability. The study found that 46% of the 72 children had brain function disorders (Manodaurbalya), 33% had nervous system disorders, 1.4% had muscular dystrophies, 1.4% had visual disorders, 1.4% had mutism disorders, and 2.7% had growth deformities. The study highlights the need for more community knowledge, better resource allocation, and focused interventions to identify and manage these children. The findings emphasize the need for research conducted in all divisional secretariats to increase awareness and support children with disabilities nationwide.